EFFECTIVENESS OF FUNDAMENTAL AND TECHNICAL ANALYSIS TECHNIQUES IN PREDICTING STOCK MOVEMENTS: A REVIEW OF THE LITERATURE AND ITS IMPLICATIONS - Hety Devita; Muhamad Eko Wahyu Umaryadi; Prawhida Surya Buana (INTERNATIONAL JOURNAL OF FINANCIAL ECONOMICS, 2024)
This study aims to review the effectiveness of fundamental and technical analysis techniques in predicting stock movements and their implications for investors. Fundamental analysis focuses on a company's financial condition, business performance, and macroeconomic factors to estimate the intrinsic value of a stock, while technical analysis uses historical price and trading volume data to identify market patterns and trends. A literature review shows that each method has advantages and limitations. Fundamental analysis is more suitable for long-term investments as it provides an in-depth view of a company's growth prospects, while technical analysis is more useful in short- and medium-term decision-making due to its ability to identify trading signals based on recent market behaviour. The conclusion of this study highlights that a combination of both techniques can support a more comprehensive and effective investment strategy, by optimising portfolio performance and minimising risk under various market conditions.